Engaging limited English proficient and ethnically diverse low-income women in health research: A randomized trial of a patient navigator intervention. Issue 7 (July 2019) - Nickell, Alyssa; Stewart, Susan L.; Burke, Nancy J.; Guerra, Claudia; Cohen, Elly; Lawlor, Catherine; Colen, Susan; Cheng, Janice; Joseph, Galen
Highlights: Low-income and LEP breast cancer survivors are willing to participate in research. Empowering individuals to seek information is not enough to engage them in research. Efforts to change the health research system are needed to facilitate inclusion. Studies must be timely, LEP accessible, and aligned with survivors' interests. Abstract: Objective: Evaluate a community-based navigator intervention to increase breast cancer patients' and survivors' access to information about health research participation opportunities. Methods: In the context of a Community Based Participatory Research collaboration, we conducted a prospective randomized controlled trial of the Health Research Engagement Intervention with pre- and post-intervention surveys (n = 133). The primary outcome was health research information-seeking behavior. Secondary outcomes were health research knowledge, willingness to participate in health research, and health empowerment. Qualitative interviews (n = 11) elucidated participant perspectives on the intervention. Results: There was no statistically significant difference between intervention and control groups' information-seeking behavior. Knowledge that not all health research studies are about drugs or treatments increased significantly from pre- to post-test among intervention group participants (32% to 48%, p = 0.012), but not in the control group (43% to 30%, p = 0.059); the difference between arms was statistically significant (p = 0.0012). Although survey responses indicated willingness to participate, qualitative interviews identified competing priorities that limited participants' motivation to seek enrollment information. Conclusions and Practice Implications: Community-based navigators are a trusted, and therefore promising link between health research and low-income underserved communities. However, systemic barriers in health research infrastructures need to be addressed to include low income, LEP and immigrant populations.